Adjusting Interfacial Chemistry and Electronic Properties of Photovoltaics Based on a Highly Pure Sb2S3 Absorber by Atomic Layer Deposition - Büttner, Pascal; Scheler, Florian; Pointer, Craig; Döhler, Dirk; Barr, Maissa; Koroleva, Aleksandra; Pankin, Dmitrii; Hatada, Ruriko; Flege, Stefan; Manshina, Alina; Young, Elizabeth R.; Minguez Bacho, Ignacio; et al. (ACS Applied Energy Materials, 2019)
The combination of oxide and heavier chalcogenide layers in thin film photovoltaics suffers limitations associated with oxygen incorporation and sulfur deficiency in the chalcogenide layer or with a chemical incompatibility which results in dewetting issues and defect states at the interface. Here, we establish atomic layer deposition (ALD) as a tool to overcome these limitations. ALD allows one to obtain highly pure Sb2S3 light absorber layers, and we exploit this technique to generate an additional interfacial layer consisting of 1.5 nm ZnS. This ultrathin layer simultaneously resolves dewetting and passivates defect states at the interface. We demonstrate via transient absorption spectroscopy that interfacial electron recombination is one order of magnitude slower at the ZnS-engineered interface than hole recombination at the Sb2S3/P3HT interface. The comparison of solar cells with and without oxide incorporation in Sb2S3, with and without the ultrathin ZnS interlayer, and with systematically varied Sb2S3 thickness provides a complete picture of the physical processes at work in the devices.
CRIS-Team Scopus Importer:2019-12-27
Keywords: antimony sulfide; atomic layer deposition; extremely thin absorber; interfacial layer; transient absorption; ultrathin layer